ISAC: A CBR System for Decision Support in Air Traffic Control - Bonzano, Andrea; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 1996)
The conflict resolution task performed by air-traffic controllers appears a suitable task for automation using CBR. This is because human competence seems to involve recognising situations and reusing solutions. In this paper we present our experiences in developing a CBR system to support this conflict resolution task. We discuss the problems of case representation: the macro problem of what should constitute a case and the micro problem of how to characterise a case. We evaluate some alternative case representations and identify a representation with one aircraft per case that is extendible to describe conflicts with multiple aircraft.
Also in I. Smyth & B. Faltings (Eds.), Advances in Case-Based Reasoning. Amstersdam: Springer-Verlag.
Keywords: Computer Science